2017
DOI: 10.1016/j.vaccine.2017.09.082
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine wastage in Nigeria: An assessment of wastage rates and related vaccinator knowledge, attitudes and practices

Abstract: Introduction The introduction of new vaccines highlights concerns about high vaccine wastage, knowledge of wastage policies and quality of stock management. However, an emphasis on minimizing wastage rates may cause confusion when recommendations are also being made to reduce missed opportunities to routinely vaccinate children. This concern is most relevant for lyophilized vaccines without preservatives [e.g. measles-containing vaccine (MCV)], which can be used for a limited time once reconstituted. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 10 publications
3
58
0
Order By: Relevance
“…The vaccine wastage rates from Bangladesh (34.8 to 84.4%) are comparable to Indian figures [16].. The wastage rates in Nigeria were in the range of 21-35% at outreach sessions and 18-27% at the stores [17]. The wastage rates were lower in Gambia for most of the vaccines, except the BCG (54.9%) [18].…”
Section: Discussionmentioning
confidence: 70%
“…The vaccine wastage rates from Bangladesh (34.8 to 84.4%) are comparable to Indian figures [16].. The wastage rates in Nigeria were in the range of 21-35% at outreach sessions and 18-27% at the stores [17]. The wastage rates were lower in Gambia for most of the vaccines, except the BCG (54.9%) [18].…”
Section: Discussionmentioning
confidence: 70%
“…Understaffing also resulted in turning children away or scheduling fewer vaccination days, further limiting the opportunities to vaccinate children. Other studies have shown that health workers might only offer certain vaccines at certain vaccination sessions and wait for a minimum number of children before opening a multi-dose vial [36,37]. Children who are unable to visit health facilities on scheduled vaccination days can be automatically excluded [13,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, observed wastage rates range between 15% to 50% for lyophilized vaccines and 5% to 25% for liquid vaccines [6]. However, studies from various low-and middle-income countries have reported high rates of vaccine wastage [7][8][9][10]. As vaccine wastage rate depends on session size, vial size, and formulation, it varies across the countries and even within the countries [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies from various low-and middle-income countries have reported high rates of vaccine wastage [7][8][9][10]. As vaccine wastage rate depends on session size, vial size, and formulation, it varies across the countries and even within the countries [7,8,10]. The systematic assessment of vaccine wastage and session size during immunization can help in deciding on optimal vial size to be procured under the immunization programme, in order to limit vaccine wastage [10].…”
Section: Introductionmentioning
confidence: 99%